MOOSFLORA OF CITY OF PRYLUKY - Гапон, Юрий; Гапон, Светлана (SWorldJournal, 2020)
The paper considers the bryoflora of Pryluky (Chernihiv region, Ukraine) and analyzes it. As a result of research it is established that the species composition of mosses of the urban ecosystem of the city and its environs includes 43 species of mosses an